Power Imbalances, Food Insecurity, and Children’s Rights in Canada - Blay-Palmer, Alison (Frontiers in Public Health, 2016)
Increasingly, food is provided through an industrial food system that separates people from the source of their food and results in high rates of food insecurity, particularly for the most vulnerable in society. A lack of food is a symptom of a lack of power in a system that privileges free market principles over social justice and the protection of human rights. In Canada, the high rates of food insecurity among Canadian children is a reflection of their lack of power and the disregard of their human rights despite the adoption of the United Nations (UN) Convention on the Rights of the Child in 1991 and ratification of the International Covenant on Social, Economic and Cultural Rights in 1976, which established the right to food for all Canadians. Dueling tensions between human rights and market forces underpin this unacceptable state of affairs in Canada. Gaventa’s ‘power cube’ that describes different facets of power – including spaces, levels and forms – is used to help understand the power imbalances that underlie this injustice. The analysis considers the impact of neo-liberal free market principles on the realization of human rights, and the negative impacts this can have on health and well-being for the most vulnerable in society. Canadian case studies from both community organizations and a novel governance initiative from the energy sector provide examples of how power can be shifted to achieve more inclusive, rights based policy and action. Given increased global pressures towards more open trade markets and national austerity measures that hollow out social supports, Canada provides a cautionary tale for countries in the EU and the US, and for overall approaches to protecting the most vulnerable in society.